2011
DOI: 10.1093/hmg/ddr205
|View full text |Cite
|
Sign up to set email alerts
|

Seipin ablation in mice results in severe generalized lipodystrophy

Abstract: Berardinelli-Seip congenital lipodystrophy type 2 (BSCL2) is an autosomal recessive disorder characterized by an almost complete loss of adipose tissue, insulin resistance and fatty liver. Here, we create the first murine model of BSCL2 by targeted disruption of seipin, the causative gene for BSCL2. Compared with their wild-type littermates, the seipin(-/-) mice are viable and of normal weight but display significantly reduced adipose tissue mass, hepatic steatosis, glucose intolerance and hyperinsulinemia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
166
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(179 citation statements)
references
References 28 publications
13
166
0
Order By: Relevance
“…We and others have established an essential role of SEIPIN in adipogenesis both in vitro and in vivo (6)(7)(8)16,17). However, SEIPIN is highly expressed in mature adipocytes, where its function is completely unknown.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We and others have established an essential role of SEIPIN in adipogenesis both in vitro and in vivo (6)(7)(8)16,17). However, SEIPIN is highly expressed in mature adipocytes, where its function is completely unknown.…”
Section: Discussionmentioning
confidence: 97%
“…Homozygous Seipin fl/fl mice were obtained as described (6). Adipose-specific deletion of Seipin exon 3 was induced by crossing Seipin fl/fl mice to transgenic mice expressing Cre recombinase driven by an aP2 promoter (18).…”
Section: Animalsmentioning
confidence: 99%
“…In contrast, the same group recently reported that pioglitazone was unable to fully restore the adipogenic programme in seipindeficient (Bscl2 −/− ) mouse embryonic fibroblast (MEF)-derived adipocytes [15]. A major breakthrough in the field of seipin came recently, with the demonstration by two independent groups that Bscl2 −/− mice develop severe lipodystrophy, validating the hypothesis that seipin has a critical role in adipocyte differentiation in vivo [15,16]. In these two models, Bscl2…”
Section: Introductionmentioning
confidence: 99%
“…In one study, Bscl2 −/− mice displayed normal plasma glucose concentrations in the random-fed state [16], while in the second, they were frankly hyperglycaemic [15]. In addition, lipid metabolism in these two models raises several questions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation